Analisis Risiko Keterlambatan Proyek Di Kabupaten Aceh Tengah - Fitra, Wina Khairunnisa; Rauzana, Anita; Mahmuddin, Mahmuddin (Journal of The Civil Engineering Student, 2023)
There are several constructions in Aceh Tengah Regency that have experienced deviations between the initial planning and the result in terms of time, cost and quality. There was many obstacles which  influence the performance of a project which therefore, inevitably, become the cause of the delays in the process of completing a project. This study was aimed at determining the risk factors that affect the time performance of project development in Aceh Tengah. This study was conducted by analysing perception data obtained from questionnaires from contractor respondents. The data of this study derived from primary and secondary data collection. The primary data were collected from questionnaires which were distributed to 57 respondents who were qualified as K1, K2, K3 and M1 contractors in Aceh Tengah. While the secondary data were in the form of supporting theories taken from books, journals and other literature. The method used in analysing the data were the Severity Index which was used to determined the level of probability and risk impact followed by  a risk matrix which used to measure the level of the risks. The results of this study showed that there were 4 dominant risk factors and 20 description of the risk factors which belonged  to the medium and high categories, namely 2 factors with medium categories are in the field of the design factor and construction factor. As well as 2 factors with high categories found in the financial factors section. Where these four factors have an impact on project time, namely the occurrence of delays or even the project can be stopped. This will increase costs so as to create a loss for the contractor.@font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;}p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:11.0pt; mso-bidi-font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-US; mso-fareast-language:EN-US;}p {mso-style-priority:99; mso-margin-top-alt:auto; margin-right:0cm; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:IN; mso-fareast-language:IN;}.MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ansi-language:IN; mso-fareast-language:IN;}div.WordSection1 {page:WordSection1;}